(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper analyses three Iberian inscriptions present on ob-jects recently donated to the Archaeological Museum of Lliria. A fragment of a lead plaque and a small lead objet allegedly both found at the Tossal de Sant Miquel (Lliria), and a fragment of a small ceramic vase with serrated cover, allegedly found at the site of Charco del Negro (Sinarcas / Benagéber) with an interesting inscription done before heating, which marks the correct closing point. Although there is a certain tradition of fakes on the environment of Llíria, in the absence of clear signs of forgery, we are inclined to believe that they are genuine pieces.